Modellgestützte Analyse des Stackbetriebs von Festoxidzellen - Russner, Niklas (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
In this work, the stack operation of solid oxide cells (SOCs) is analyzed by a simulation model. For this purpose, all coupled physical and chemical sub-processes are represented within a two-dimensional geometry of a single stack level. After parameterization with experimental data and extensive validation, the model is applied to three research issues in SOC technology.